2020
DOI: 10.1111/medu.14427
|View full text |Cite
|
Sign up to set email alerts
|

Gender in authorship and editorship in medical education journals: A bibliometric review

Abstract: Context Gender bias has been observed in the authorship and editorship of academic literature in varied medical specialties. This is important as peer‐reviewed publications, and participation on editorial boards, are closely related to academic productivity and advancement. The aim of this paper was to examine whether gender‐based disparities in authorship and editorship exist in leading medical education journals. Methods A retrospective bibliometric review was conducted of articles published at eight differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 45 publications
8
52
1
1
Order By: Relevance
“…Additionally, gender parity among authorship teams has been achieved in recent years, which aligns with Madden's recent analysis of four medical education journals across a variety of publication types. 21 Furthermore, similar to the findings from Madden et al examining other medical specialities, [44][45][46] we identified significantly more males in the last author position. In biomedicine, the last position is traditionally occupied by the senior author who takes on a leadership role in the study 47 or is often the principal investigator of the research laboratory conducting the work.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Additionally, gender parity among authorship teams has been achieved in recent years, which aligns with Madden's recent analysis of four medical education journals across a variety of publication types. 21 Furthermore, similar to the findings from Madden et al examining other medical specialities, [44][45][46] we identified significantly more males in the last author position. In biomedicine, the last position is traditionally occupied by the senior author who takes on a leadership role in the study 47 or is often the principal investigator of the research laboratory conducting the work.…”
Section: Discussionsupporting
confidence: 89%
“…However, this is a starting point necessary to begin to provide a sense of the field and follows the protocol of similar papers published on this topic. 21,61…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Medical Education is an international journal with readers, reviewers and authors from all corners of the globe 4 . We are not focused on any particular specialty, any particular health profession, nor any particular level of training/practice.…”
Section: Generalmentioning
confidence: 99%